Homosexuality: maly testimonies - Bruns, Maria A.T.; Marque, Cristiane R. (Brazilian Journal of Sexually Transmitted Diseases, 2002)
The objetive of this study was to understard how some men experience homosexuality in our age, or what significance they attribute to their own experienceof this phenomenon. Seven men in the 40 to 50 years old age group who were declared homosexuals were interviewed. Their testimonies were submittedto qualitative phenomenological analysis and the theoretical-philosophical Martin Buber standard. Their discourses revealed that in the process of theirown identification as homosexuals in spite of their feeling the target of prejudice, they perceived themselves as being stygmatized by society, refusing toincorporate a stereotyped personality preferring to search for social integration instead of living in ghettos.